Produktivitas Kedelai pada Lahan Bekas Pemupukan Nitrogen Beberapa Varietas Padi Sawah Irigasi - Girsang, Setia Sari; Nurzannah, Sri Endah (Jurnal Penelitian Pertanian Tanaman Pangan, 2021)
Soybeans are generally cultivated in irrigated and rainfed rice fields after rice harvest and on dry land. This study aims to determine the effect of N fertilizer and several rice varities residues on lowland rice field on the growth and yield of soybean crops. The research was conducted on rice fields after rice harvest in Serdang Village, Beringin District, Deli Serdang Regency (3035â€™55,90â€ South Latitude 98053â€™58,24â€ East longitude with an elevation of 2.4-meters above sea level). The soybean used is the kipas putih variety. Factorial randomized block design with two factors and three replications. The factor consists of three varieties (V), namely: (V1) Inpari-32, (V2) Inpari-42, and (V3) Inpari IR Nutri Zinc. The second factor consists of seven different doses of N fertilization treatments (P), namely: without N (P1), low N is 95 kg/ha (35-30-30) (P2), standard N is 125 kg/ha (35-45-45) (P3), high N is 155 kg/ha (35-60-60) (P4), standard N with highest N at primordial is 125 kg/ha (35-30-60) (P5), standard N + additional N 30 kg/ha at primordial (35-45-75) (P6), and standard N + additional N 30 kg/ha after primordial (booting stage) with 4 times applicationis 155 kg/ha (35-45-45-30) (P7). Plot size is 5 m x 5 m and between the plots a drainage channel is made of width 0.5 m and depth 0.4 m. Soybean spacing is 0.4 m x 0.2 m and the previous cropping distance when planting rice is 0.2 m x 0.2 m by planting two seeds per hole as well as liquid organic fertilizer applications conducted at 30 and 50 DAP respectively of 315 ml/63 liters of water. The research result indicates the need for N fertilizer on soybean crop after rice in paddy fields with medium soil fertility is not determined by previously planted rice varieties. To achieve optimum soybean yields for each of the former new superior rice varieties, the residue of N fertilization in rice was 125 kg/ha with three times of application according to the plant growth stages plus additional N during booting stages of 30 kg/ha (total 155 kg/ha) in wet season that contribute significantly to increased growth and productivity of soybean on land with medium soil fertility, soybean-rice-rice cropping pattern, and uniform land management.